A case of laparoscopic sigmoidectomy using thermography for colonic blood flow assessment - Tomohiro Kako; Masahiro Kimura; Ryo Nomura; Shuhei Uehara; Hiroshi Uematsu; Seiichi Nakaya; Yuzo Maeda; Ken Tsuboi; Koshiro Harata; Shuji Takiguchi (Surgical Case Reports)
Abstract Background Indocyanine green (ICG) fluorescence imaging is widely used in gastrointestinal surgery and is considered useful for reducing anastomotic leakage; however, because ICG remains in the tissue for a certain amount of time, we occasionally must re-evaluate colonic blood flow over a short time period during surgery. Herein, we verify the usefulness of thermography (TG) for evaluating colonic blood flow in a patient who underwent a laparoscopic sigmoidectomy for sigmoid colon cancer. Case presentation The patient is 43-year-old man who underwent laparoscopic resection of the sigmoid colon for colon cancer. After vascular treatment of the colonic mesentery, ICG/TG identified the boundary between ischemic and non-ischemic colon tissues. An additional 2 cm of colonic mesentery was resected because of the presence of a diverticulum noted at the intended site of oral anastomosis when attaching the anvil head. After additional vascular treatment of the colonic mesentery and administration of ICG, fluorescence was observed in the colon; however, TG identified the zone of the temperature transition on the surface of the colonic mesentery, even after additional colonic mesentery resection in the same region as previously observed. This zone was used as the cut-off line. There were no complications, such as anastomotic leakage, after the surgery. Conclusion Although accumulation of similar cases is necessary, TG has the potential for use as an auxiliary diagnostic tool in clinical practice. TG can depict the presence or absence of blood flow based on surface temperature without the use of imaging agents, and is inexpensive and easy to perform.